Sosialisasi Pengembangan Sumber Daya Manusia Pada Koperasi KSOP Betik Hati Bandar Lampung - Yudhinanto CN; Holdin Sagita (BADAN PENERBIT STIEPARI PRESS, 2023)
Community service activities to provide socialization of Human Resource development activities are carried out at the Betik Hati KSOP Cooperative. activity method with material presentation, discussion. a series of community service activities. The method used is direct socialization and material training as well as discussions regarding the application of HRM in developing human resources for managers and administrators of the Betik Hati KSOP cooperative based on the results of activities where good management will produce good human resources and produce capable human resources. and great skills. With all the problems it faces will affect the performance of these resources, both physically and psychologically in achieving a goal.